The Influence of Facilities, Work Environment, and Job Placement on Employee Motivation at BKPSDM Gresik - Faishal Reza Saputra; Mochamad Syafii; Rachmad Ilham (Lembaga Pengembangan Kinerja Dosen, 2025)
Low employee motivation remains a persistent issue in many public institutions, including the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) of Gresik Regency, where challenges related to inadequate facilities, suboptimal work environments, and misaligned job placements have been identified. This study investigates the extent to which these three organizational factors—facilities, work environment, and placement—influence employee motivation. A quantitative research approach was employed using a saturated sample of 49 civil servants, with data collected via structured Likert-scale questionnaires and analyzed through multiple linear regression. The results indicate that all three variables significantly and positively affect motivation, with the work environment having the strongest influence, followed by facilities and placement. The model explains 64.6% of the variation in employee motivation, underscoring the central role of institutional conditions in shaping staff engagement. While BKPSDM has introduced initiatives such as GAPURA to support professional development, notable gaps remain in basic infrastructure, environmental comfort, and strategic role assignment. These findings highlight the urgent need for targeted interventions in workspace design, equipment modernization, and competency-based placement strategies. The study provides practical guidance for government managers seeking to improve workforce morale and productivity. Future research should consider longitudinal designs and incorporate organizational culture and leadership as mediating variables to deepen understanding of motivation drivers in the public sector.